1992
DOI: 10.1164/ajrccm/146.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urinary Cotinine Level and Diagnosis in Children Admitted to Hospital

Abstract: The reported association between passive smoking and respiratory illness in children has been based on the parents' assessment of their own level of smoking. To more critically evaluate a causal relationship between passive smoking and childhood ill health, we used urinary cotinine, which is the major metabolite of nicotine and has a long half-life, to objectively quantitate the level of passive smoking in children. Urine was collected from 609 children (median age 3.8 yr, range 1 month to 17 yr) on admission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
2
36
1
Order By: Relevance
“…22 Another study linked urine cotinine levels to hospitalizations for bronchiolitis in infants. 23 The current study lends additional support to an emerging role for cotinine measurements as a biomarker and potential clinical measure for predicting future hospitalizations in children, especially those with respiratory conditions.…”
Section: Discussionsupporting
confidence: 54%
“…22 Another study linked urine cotinine levels to hospitalizations for bronchiolitis in infants. 23 The current study lends additional support to an emerging role for cotinine measurements as a biomarker and potential clinical measure for predicting future hospitalizations in children, especially those with respiratory conditions.…”
Section: Discussionsupporting
confidence: 54%
“…37 Surprisingly, parental smoking does not increase the risk of hospital admission for acute asthma.263238 Reese et al found no association between urinary cotinine levels and asthma admissions, but they reported a positive correlation with admissions for bronchiolitis. 26 Ehrlich et al showed a correlation between recent passive smoking (as assessed by questionnaire and urinary levels of cotinine) and a diagnosis of asthma, but no association with acute exacerbations.38 They suggested that passive smoking increases hyperreactivity rather than producing bronchospasm.…”
Section: Passive Smoking Wheeze and Asthmamentioning
confidence: 99%
“…Female smokers in the Israeli army had a 60% risk of influenza, compared with a 41.6% risk in nonsmokers (7). In addition, neonates and children exposed to cigarette smoke have a higher incidence and severity of viral infection (8)(9)(10)(11). These epidemiologic studies suggest that smoking is a risk factor for severe viral infection; however, the mechanism(s) for this are not known.…”
mentioning
confidence: 99%